PEMERIKSAAN HIV (Human Immunodeficiency Virus) NARAPIDANA YANG DIRUJUK PADA RUMAH SAKIT BHAYANGKARA TK I JAYAPURA PAPUA - Taroreh, Jannete Elisabeth; Romadhonni, Tika; Rampa, Ester; Balabuana, Gaspar Bao; Sinaga, Herlando; May, Matilda Bernadece (Universitas Cokroaminoto Palopo, 2025)
This study was entitled HIV Examination in prisoner patients referred to Bhayangkara Hospital TK II Jayapura City. The purpose of this study was to determine HIV infection in serum samples of inmate patients. This type of research is descriptive with a laboratory test approach. This study was conducted for 3 months starting from October 15, 2024 to January 15, 2025. The population and the number of samples used were all inmate patients who conducted examinations at the Bhayangkara TK II Jayapura City Hospital and the number of samples used in this study were 30 samples. The sample used is the serum of inmate patients. The examination method used is the Rapid Diagnostic Test Antibody Method using the Rapid Test tool ViroChek HIV 1/2 brand. The results showed that HIV testing in inmate patients from 30 samples showed Reactive results as many as 3 samples (10%) and 27 (90%) Non Reactive.